ETNOMATEMATIKA DALAM TRADISI PERNIKAHAN ADAT SUKU DAYAK KALIS DI KECAMATAN KALIS KABUPATEN KAPUAS HULU - Konstansia Katlin Stevani; Agung Hartoyo; Munaldus Munaldus (Jurnal AlphaEuclidEdu, 2022)
This study aims to describe the implementation of the stages of the traditional marriage tradition of the Dayak Kalis tribe in Nanga Danau village, Kalis sub-district, Kapuas Hulu district, and to find out of what mathematical activities are include in the implementation of the stages of the traditional wedding tradition. The form of research used is qualitative research with an ethnographic approach. The subjects in this study consisted of three subjects, the first being the traditional chief at the hamlet level, the second subject at the village level, and the third being an elder traditional leader. Data collection techniques used are interview, documentation, and observation techniques. The data collection tools used were interview guides, observation guidelines, cellphone cameras and voice recorders. The result and analysis of the data obtained from this study are (1) At the stage of the Situtukang Baba’ and Paseset activities there is an activity to explain. (2) At the stage of Baru-Baru there are activities to explain, determine location, and count. And the mathematical concepts contained in it are the concepts of counting, the concept of logic, the concept of multiplication, and the concept of multiples.